(untitled) (Fiep Bulletin - online, 2011)
This article aims to analyze the attitude of teachers and their continuing education through a literature perspective. The research is the expression of knowledge, unfinished, and the main activity of science which it (research) food for education activities, an educational reality facing the world, guided by the scientific thinking, always trying to build, giving active life education. The teacher must practice research to teach didactically and effectively, students need to make use of research to significantly build their own thought, society at large needs to have the research that we might call the result of product knowledge, the University of turn requires the research to be the mediator of education, and fulfill its role in the educatioal triad "teaching, research extension. These being the main exercises of science, which is characterized in this constant sarch for scientific knowledge. Here the teacher needs to support the continuity of their education, to this healthy and the desire for change and innovation, producing knowledge as epistemic subject. The benefits of the research lead us into the realm of critical production of knowledge, helps us learn to teach ourselves and others conducting research professor refute the confidence in the procedures of thought already known and experienced, meeting the new knowledge or reformulating existing ones, making you be creative in a world of knowledge teaching. The survey creates an analytic work to make consistent, practical, pleasing to art education in these aspects and methodological paradigms that must be concatenated with the various activities of scientific initiation of production of knowledge, and building faculty researchers, overlooking the improvement and significant experience in teacher education researchers, reflecting joy, well being and strength as educators, researchers in a country like Brazil, with many professionals in universities.